A PROSPECTIVE STUDY ON RISK FACTORS OF IRON DEFICIENCY ANEMIA IN PREGNANT WOMEN AND THEIR MANAGEMENT - KUMAR, R. DINESH; RAJA, M. BOOPATHI; P. S., SREEVEENA; MATHEW, RACHEL ANN (International Journal of Current Pharmaceutical Research, 2020)
Objective: Iron deficiency anemia during pregnancy leads to preterm birth, low birth weight and increases the incidence of postpartum hemorrhage (PPH) and the reason for the incidence of PPH is higher in India compared with the rest of the world. In this study, our main goal was to find out the risk factors and complications of iron deficiency anemia and their management in pregnant women. Methods: It is a prospective study done at Obstetrics and Gynecology Department in Government District Headquarters Hospital, Tiruppur. All subjects were analyzed in full detail and hemoglobin estimation was also done to the patients. Results: Study found that 52% shows moderate anemia followed by 30% mild and 18% severe, respectively. Risk factors are found in 55% cases. Study found an association between risk factors and severity of anemia. Conclusion: Iron deficiency anemia continues to be the commonest etiology of anemia in pregnancy. The prevalence of iron deficiency in a pregnant woman is amongst the highest in the world. Untreated iron deficiency has significant adverse feto-maternal consequences. Iron supplementation and antenatal care are the basic requirements to prevent anemia.